Regulatory Considerations Specific to Liposome Drug Development as Complex Drug Products - Wang, Yuwei; Grainger, David W. (Frontiers in Drug Delivery, 2022)
Nearly a half-century after original liposome discovery as a prospective lipid pharmaceutical carrier, the global liposomal drug delivery market has increased dramatically, with an annual market growth rate of 13.2%, valued at ~$6993 million by 2027. As an intrinsically complex delivery system, liposomal formulations face much greater characterization and regulatory review challenges than traditional small molecule drugs and biologics. Due to rapid liposomal drug development, both European Medicines Agency (EMA) and US Food and Drug Administration (FDA) now provide regulatory guidance for new liposomal drug application reviews. The expanding global liposome drug market and associated driving forces for increased research and development (R&D) in novel liposomal products are key factors propelling liposomal drug interests. We review and compare EU and US regulations on liposomal drug submissions, and provide insights into regulatory strategies throughout the entire liposomal drug development process. This addresses current gaps noted between liposome-based drug development in research labs and current regulatory guidance for liposomal drug approvals in order to facilitate more efficient, less costly, and less risky complex drug development.